PfCHA is a mitochondrial divalent cation/H+ antiporter in Plasmodium falciparum - Rotmann, Alexander; Sanchez, Cecilia P.; Guiguemde, Armand; Rohrbach, Petra; Dave, Anurag; Bakouh, Naziha; Planelles, Gabrielle; Lanzer, Michael (Molecular microbiology, 2010)
The human malaria parasite Plasmodium falciparum is capable of adapting to vastly different extracellular Ca2+ environments while maintaining tight control of its intracellular Ca2+ concentration. The mechanisms underpinning Ca2+ homeostasis in this important pathogen are only partly understood. Here we have functionally expressed the putative Ca2+/H+ antiporter PfCHA in Xenopus laevis oocytes. Our data suggest that PfCHA mediates H+-coupled Ca2+ and Mn2+ exchange. The apparent dissociation constant KM for Ca2+ of 2.2 ± 0.7 mM and the maximal velocity Vmax of 0.6 ± 0.1 nmol per oocyte per hour are consistent with PfCHA being a low-affinity high-capacity Ca2+ carrier. In the parasite, PfCHA was found to localize to the mitochondrion. Physiological studies conducted with live parasitized erythrocytes, and using Fluo-4 and Rhod-2 to monitor cytoplasmic and mitochondrial Ca2+ dynamics, suggest that the mitochondrion serves as a dynamic Ca2+ store and that PfCHA functions as a Ca2+ efflux system expelling excess Ca2+ from the mitochondrion. PfCHA lacks appreciable homologies to the human mitochondrial Ca2+/H+ exchanger and might represent an evolutionary divergent class of mitochondrial cation antiporter, which, in turn, might provide novel opportunities for intervention.